Sex-dependent differences in growth of vascular smooth muscles cells from spontaneously hypertensive rats - Bacáková, L; Kunes, J (Physiological research, 1995)
The growth capacity of cultured vascular smooth muscle cells (VSMC) obtained from the thoracic aorta of 8-week-old male and female spontaneously hypertensive rats (SHR) was compared. Explants from the intima-media complex were cultured in Dulbecco minimum essential medium supplemented with fetal calf serum (10%). The migration of VSMC out of the explants started on day 2 in both sexes but on day 18 the number of explants with VSMC migration was 100 +/- 32 explants/flask in male VSMC and only 24 +/- 5 explants/flask in female ones. The doubling time at the early exponential phase of growth was shorter (13.5 +/- 0.5 h) and the [3H]-thymidine Labelling Index was higher (34.0 +/- 2.3%) in male VSMC than in those from females (19.9 +/- 0.6 h and 23.9 +/- 1.9%, p < 0.01, respectively). The difference in the doubling time became even more apparent in the late exponential phase of growth (male VSMC: 51.8 +/- 2.0 h, female VSMC: 91.5 +/- 5.8 h, p < 0.001). Moreover, at the end of the exponential growth phase, the male VSMC reached significantly higher (p < 0.001) maximum population density than VSMC from females. Our data provide evidence of different growth characteristics of cultured VSMC isolated from male and female SHR aortas.
Keywords: Thymidine; Cell Division; rozložení podle pohlaví; tritium; Female; svaly hladké cévní; krysa rodu Rattus; zvířata; Cells, Cultured; thymidin; ženské pohlaví; krevní tlak; Male; potkani inbrední SHR; Tritium; kultivované buňky; Rats; Sex Distribution; Body Weight; Animals; tělesná hmotnost; mužské pohlaví; Muscle, Smooth, Vascular; Blood Pressure; Rats, Inbred SHR; buněčné dělení